Odpowiedź:
a.
[tex]\frac{1}{3}x-2= x+2 / *3\\x-2=3x+2/-x\\-2=2x+2/-2\\-4=2x/:2\\-2=x[/tex]
b.
[tex]1-\frac{6}{7}x=\frac{4}{7}/*7\\7-6x=4\//-7\\-6x=-3\//: (-6)\\x=\frac{1}{2}[/tex]
c.
[tex]6(\frac{1}{4} x-2)=18/:6\\\\\frac{1}{4} x-2=3/*4\\x-8=12/+8\\x=20[/tex]
d.
[tex]\frac{x}{6} -\frac{1}{6} =1/*6\\x-1=6/+1\\x=7[/tex]
e.
[tex]2(2x-1)=\frac{x}{3}\\ 4x-2=\frac{x}{3}/*3\\12x-6=x/+6\\ 12x=x+6/-x\\11x=6/:11\\x=\frac{6}{11}[/tex]
f.
[tex]\frac{2}{5}(3-x)=-2 \\\\\frac{6}{5}-\frac{2}{5}x = -2/*5\\ 6-2x= -10/-6\\ -2x=-16/:(-2)\\x=8[/tex]